Real evaporative cooling efficiency of one-layer tight-fitting sportswear in a hot environment - Wang, F.; Annaheim, S.; Morrissey, M.; Rossi, R. M. (Scandinavian journal of medicine & science in sports, 2014)
Real evaporative cooling efficiency, the ratio of real evaporative heat loss to evaporative cooling potential, is an important parameter to characterize the real cooling benefit for the human body. Previous studies on protective clothing showed that the cooling efficiency decreases with increasing distance between the evaporation locations and the human skin. However, it is still unclear how evaporative cooling efficiency decreases as the moisture is transported from the skin to the clothing layer. In this study, we performed experiments with a sweating torso manikin to mimic three different phases of moisture absorption in one‐layer tight‐fitting sportswear. Clothing materials Coolmax® (CM; INVISTA, Wichita, Kansas, USA; 100%, profiled cross‐section polyester fiber), merino wool (MW; 100%), sports wool (SW; 50% wool, 50% polyester), and cotton (CO; 100%) were selected for the study. The results demonstrated that, for the sportswear materials tested, the real evaporative cooling efficiency linearly decreases with the increasing ratio of moisture being transported away from skin surface to clothing layer (adjusted R2 >0.97). In addition, clothing fabric thickness has a negative effect on the real evaporative cooling efficiency. Clothing CM and SW showed a good ability in maintaining evaporative cooling efficiency. In contrast, clothing MW made from thicker fabric had the worst performance in maintaining evaporative cooling efficiency. It is thus suggested that thin fabric materials such as CM and SW should be used to manufacture one‐layer tight‐fitting sportswear.